show that

Asked by shekhar14351 | 12th Feb, 2010, 09:30: PM

Expert Answer:

(x-123)(x-4) +(x-11)(x-14) +(x-2)2=0

Expanding out and collecting the terms of the quadratic equation,

3x2 - 156x + 700 = 0

The product of the roots, by comparing with x2+(α+β) + αβ = 0,

is 700/3.


(x-123)(x-4) +(x-11)(x-14) +(x-2)(x-2)=0

Product of the roots = Σproduct of constant terms/total number of products.

= ((-123)(-4)+(-11)(-14)+(-2)(-2))/3 = 700/3

Use this only for qudratic equation.






Answered by  | 13th Feb, 2010, 06:38: AM

Queries asked on Sunday & after 7pm from Monday to Saturday will be answered after 12pm the next working day.